2009
DOI: 10.1210/jc.2008-1747
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Incremental Value of Recombinant Thyrotropin Stimulation before 2-[18F]-Fluoro-2-Deoxy-d-Glucose Positron Emission Tomography/Computed Tomography Imaging to Localize Residual Differentiated Thyroid Cancer

Abstract: The use of rhTSH for 2-[18F]-fluoro-2-deoxy-D-glucose-PET/CT significantly increased the number of lesions detected, but the numbers of patients in whom any lesion was detected were no different between basal and rhTSH-stimulated PET/CT scans. Treatment changes due to true positive lesions occurred in 6% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 29 publications
7
66
3
6
Order By: Relevance
“…As a matter of fact, more important than the influence of rhTSH or thyroid hormone withdrawal in 18 F-FDG PET/CT is the presence of high levels of Tg (Tg/ TSH or Tg/LT4 > 10 ng/mL). Over the last years, it has been demonstrated that both strategies, with or without TSH stimulation, do not considerably lead to management changes (12,32). Additional factors than sTg that influence 18 F-FDG PET/CT sensitivity are tumor de-differentiation and larger tumor burden (6), as we have seen in our results.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…As a matter of fact, more important than the influence of rhTSH or thyroid hormone withdrawal in 18 F-FDG PET/CT is the presence of high levels of Tg (Tg/ TSH or Tg/LT4 > 10 ng/mL). Over the last years, it has been demonstrated that both strategies, with or without TSH stimulation, do not considerably lead to management changes (12,32). Additional factors than sTg that influence 18 F-FDG PET/CT sensitivity are tumor de-differentiation and larger tumor burden (6), as we have seen in our results.…”
Section: Discussionsupporting
confidence: 58%
“…Patients with histological findings of aggressive DTC variants (n = 21): oncocytic (n = 3), poorly differentiated areas (n = 2), tall-cell (n = 4), diffuse sclerosing (n = 4), insular (n = 5) and solid variant (n = 3) with incomplete biochemical or structural disease. (12,14). Consequently, the remaining 36 scans were performed using LT4 (Tg/LT4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Petrich et al found that the number of positive scans, as well as the number of lesions and standardized uptake values (SUV), increased with the use of rhTSH stimulation (28). In contrast, Leboulleux et al found that the number of positive scans did not increase, but the number of identified lesions did increase after stimulation with rhTSH; the increased number of lesions changed management in about 6% of cases (29). Despite studies showing that sensitivity of PET imaging improves under TSH stimulation, a high proportion of PET scans being done without stimulation was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence from a number of studies of resected thyroid tissue suggests that TSHR is more persistently expressed than other differentiation markers, including NIS and thyroglobulin proteins , Lazar et al 1999, Gerard et al 2003, indicating not only that TSHR may remain an important signaling pathway for cellular growth but also its utility as a conserved therapeutic target. Further in vivo evidence of continued TSHR expression in the absence of NIS is provided by a study of 63 patients with metastatic DTC, and no radioactive iodine uptake on whole body scan, who underwent 18 F-fludeoxyglucose positron emission tomography ( 18 F-FDG-PET) both under basal conditions and after rhTSH stimulation (Leboulleux et al 2009). This study found that the sensitivity of FDG-PET was significantly increased after rhTSH stimulation on a per lesion basis (95% vs 81%), suggesting that these lesions continued to express TSHR in the absence of the ability to concentrate radioiodine.…”
Section: Persistence Of Tshr Expression In the Setting Of Loss Of Othmentioning
confidence: 99%